2001
DOI: 10.1021/jf010556l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Food Reductones, 2,5-Dimethyl-4-hydroxy-3(2H)-furanone (DMHF) and Hydroxyhydroquinone (HHQ), on Lipid Peroxidation and Type IV and I Allergy Responses of Mouse

Abstract: The effect of long-term supplementation of food reductones, 2,5-dimethyl-4-hydroxy-3(2H)-furanone (DMHF) (2%, w/w), detected in many foodstuffs including soy sauce, and hydroxyhydroquinone (1,2,4-benzenetriol) (HHQ) (1.2%, w/w), detected in coffee, on mouse lipid peroxidation and type IV and I allergy responses was investigated. The effect of supplementation of these reductones combined with NO(2) inhalation (5-6 ppm) was also investigated. Levels of thiobarbituric acid-reactive substances in lung were remarka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Long-term supplementation of the component to mice increased lung lipid peroxidation, whereas it decreased liver and kidney lipid peroxidation. 16) Supplementation of the component to rats induced lung and heart lipid peroxidation (unpublished results). Supplementation to mice increased allergen-induced type IV contact allergy responses and type I respiratory allergy responses.…”
Section: Fig 4 Time Course Of the Increase In Hydrogen Peroxide Levmentioning
confidence: 90%
See 2 more Smart Citations
“…Long-term supplementation of the component to mice increased lung lipid peroxidation, whereas it decreased liver and kidney lipid peroxidation. 16) Supplementation of the component to rats induced lung and heart lipid peroxidation (unpublished results). Supplementation to mice increased allergen-induced type IV contact allergy responses and type I respiratory allergy responses.…”
Section: Fig 4 Time Course Of the Increase In Hydrogen Peroxide Levmentioning
confidence: 90%
“…14,15) Animal studies of the compound have shown that long-term supplementation of the component to mice remarkably induces lung lipid peroxidation, and enhances type IV and I allergy responses. 16) Our previous study has demonstrated that roasted coffee beans contain 1,2,4-benzenetriol as a major hydrogen peroxide-generating component, causing DNA single strand breaks. 8,9) The presence of this component in coffee has been clarified by its isolation from the complex coffee mixture.…”
Section: Fig 4 Time Course Of the Increase In Hydrogen Peroxide Levmentioning
confidence: 99%
See 1 more Smart Citation
“…NO and inflammatory mediators, such as tumor necrosis factor-a (TNF-a) released from LPSactivated microglia can damage dopaminergic neurons [15]. The long-term supplementation of BT (1.2%, w/w) increases mouse lipid peroxidation and type IV and I allergy responses [16].…”
Section: Introductionmentioning
confidence: 99%
“…The compound is mutagenic to Salmonella bacteria (10) and cleaves DNA single strands (3)(4)(5)(6)(7)(8)(9) in the in vitro studies, which is suggested to participate in the carcinogenicity of ben-zene (9). It has been shown that long-term supplementation of the component to mice increases lung lipid peroxidation and enhances type IV and I allergy responses (11).…”
Section: Introductionmentioning
confidence: 99%